Rapid fluvial incision and headward erosion by the Yellow River along the Jinshaan gorge during the past 1.2 Ma as a result of tectonic extension. (1st February 2016) - Hu, Zhenbo; Pan, Baotian; Guo, Lianyong; Vandenberghe, Jef; Liu, Xiaopeng; Wang, Junping; Fan, Yunlong; Mao, Junwei; Gao, Hongshan; Hu, Xiaofei
Abstract: In North China, the Ordos block located northeast of the Tibetan Plateau is regarded as a stable craton surrounded by the Yinchuan graben to the west, the Hetao graben to the north, and the Fenwei graben to the southeast. The major tectonic structure around this block in the Cenozoic reflects intensive extension as a response to the eastward extrusion of the Tibetan Plateau. Intermittent downcutting by the Yellow River, starting from the planation surface level on the Ordos block and penetrating the bedrock, resulted in the formation of the Jinshaan gorge. A series of well-preserved fluvial terraces was identified along this gorge, providing new insight into the far-field effect of the eastward extrusion of the Tibetan Plateau. Magnetostratigraphic records from the planation surface and uppermost terrace suggest that this gorge has been entrenched over its total length in the period from 3.7 to 1.2 Ma. A preliminary explanation is proposed here for the morphological evolution of the Yellow River in the Jinshaan gorge. On the basis of terrace correlation between seventeen geomorphic sections, multiwave headward erosion initiated by the Yellow River along this gorge has been reconstructed. This process may be attributed to the lowering of the base level (the Fenwei graben). This graben has been formed during the Cenozoic as the Tibetan Plateau extruded eastwards resulting in accelerated ground subsidence. A combined approach of magnetostratigraphy, pedostratigraphy, and optically stimulated luminescence (OSL) was adopted to establish a new geochronology for terraces in the gorge at 1.2 Ma, 1.1 Ma, 787 ka, 412 ka, 245 ka, 128 ka, 29 ka, and 11 ka. These ages provide an excellent framework for calculating the extension within the Fenwei graben. The average incision rate appears to be enhanced significantly since 412 ka, indicating a rapid extension within the Fenwei graben during this time. Highlights: We reconstructed a 1.2 Ma sequence based on the terraces in the Jinshaan gorge, North China. Multiwave headward erosion of the Yellow River in this gorge was outlined by terrace correlation. The extensional tectonics provides a potential explanation for the multiwave headward erosion. This landscape evolution may be associated with the eastward extrusion of the Tibetan Plateau. The average incision rate reveals the accelerated eastward extrusion of the Tibetan Plateau.